Enhancing Innovation and Underlying Neural Mechanisms Via Cognitive Training in Healthy Older Adults - Chapman, Sandra B.; Spence, Jeffrey S.; Aslan, Sina; Keebler, Molly W. (Frontiers in Aging Neuroscience, 2017)
Non-invasive interventions, such as cognitive training and physical exercise, are gaining momentum as ways to augment both cognitive and brain function throughout life. One of the most fundamental yet little studied aspects of human cognition is innovative thinking, especially in older adults. In this study, we utilize a measure of innovative cognition that examines both the quantity and quality of abstracted interpretations. This randomized pilot trial in cognitively normal adults (56-75 years) compared the effect of cognitive reasoning training (SMART) on innovative cognition as measured by Multiple Interpretations Measure (MIM). We also examined brain changes in relation to MIM using two MRI-based measurements of arterial spin labeling (ASL) to measure cerebral blood flow and functional connectivity MRI to measure default mode and central executive network synchrony at rest. Participants (N = 58) were randomized to the cognitive training (CT), physical exercise (PT) or control (CN) group where cognitive training and physical training groups received training for 3 hours per week over 12 weeks. They were assessed at baseline-, mid-, and post-training using innovative cognition and MRI measures. First, the cognitive training group showed significant gains pre- to post-training on the innovation measure whereas the physical exercise and control groups failed to show significant gains. Next, the cognitive training group showed increased cerebral blood flow in medial orbitofrontal cortex (mOFC) and bilateral posterior cingulate cortex (PCC), two nodes within the Default Mode Network (DMN) compared to physical exercise and control groups. Last, significant correlations were found between innovation performance and connectivity of two major networks: Central Executive Network (CEN, positive correlation) and Default Mode Network (DMN, negative correlation). These results support the view that both the CEN and DMN are important for enhancement of innovative cognition. We propose that neural mechanisms in healthy older adults can be modified through reasoning training to better subserve enhanced innovative cognition.